Fabrication And Characterisation Of Graphene-Poly (3-Hydroxybutyrate-Co-4-Hydroxybutyrate) Bioactive Glass Composite For Potential Wound Healing - Rahim, Mohd Aiman Hakimi Abd (2024)
Managing wounds clinically presents a notable challenge. It involves not only ensuring that the dressing provides necessary barrier and promotes healing but also requires consideration of patient compliance in term of comfort, functionality, and practicality. Poly(3-hydroxybutyrate-co-4-hydroxybutyrate) is a bacterial derived biopolymer widely notable for its exceptional chemical, physical, and mechanical properties. P(3HB-co-4HB) is widely known to be biodegradable and highly biocompatible. However, P(3HB-co-4HB) copolymer has its limitation as it exhibits hydrophobic properties, thus restrict its potential in regenerative medicine. Improving materials can address specific limitations within polymer matrices, such as hydrophilicity, mechanical behaviour, and morphological structure as well as biocompatibility. In pursuit of this goal, bioactive glass and graphene were integrated into the scaffold to enhance the physicochemical characteristics of the P(3HB-co-4HB) copolymer. Bioactive glass (BG) is recognised for its ability to stimulate vascularisation and regulate anti-inflammatory molecules and growth factor upon the release of its ions, which on turn enhances the process of wound healing. Graphene is known to possess excellent electrical, mechanical, thermal, chemical properties, and high surface area. It was synthesised using the liquid-phase exfoliation technique, which is a dependable approach for obtaining high quality graphene and economically viable.